A predictive tool to evaluate disc brake squeal propensity. Part 2: System linearisation and modal analysis. (20th February 2004) - Lee, Y.S.; Brooks, P.C.; Barton, D.C.; Crolla, D.A.
This paper is the second in a series of three that together describe an integrated theoretical approach to the analysis of disc brake squeal. Within this paper, the specific problems of system linearisation and complex modal analysis are addressed. The likelihood of squeal noise occurrence is quantified by the definition of a single indicator derived from the system eigenvalues. Mode shape analysis permits study of the motion linked to each mode and a technique is presented that reconstructs a true picture of the complex mode through the combination of its real and imaginary components. Typical results are presented for stable and unstable modes of vibration which lead to the proposal of a mechanism that gives rise to the unstable squeal vibration.